INTEGRASI AGAMA DAN SAINS DALAM PERSPEKTIF ZIAUDDIN SARDAR: KRITIK TERHADAP PARADIGMA SAINS MODERN - Syahfitri, Imeldha; Calista Ramadhani, Auryn; Amril M; Novita, Liana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the integration of religion and science from Ziauddin Sardar's perspective through his critique of the modern scientific paradigm. Modern science is considered to be secular and neglects spiritual values, giving rise to various ethical and humanitarian issues. The method used is a literature review with a qualitative approach. The results of the study indicate that Ziauddin Sardar critiques the dominance of the Western paradigm in science and offers an integration that balances revelation, reason, and empiricism. This integration aims to create a science that is more ethical, humanistic, and oriented towards the welfare of humanity.